Pengaruh Keamanan Konsumen Terhadap Kepercayaan Sebagai Variabel Intervening (Studi Pada Mahasiswa UnHar Pelanggan Shopee) - Tasya Nurul Annisa; Saskia Yusuf; Sunaryo (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2022)
This research was conducted with the aim of knowing whether or not there is an influence of consumer safety and quality of information on purchasing decisions with trust as an intervening variable. Aimed at students of Harapan Medan University as customers of beauty products through Shopee.Based on the SPSS output with the Standardized Coefficients Beta value, it shows that, Consumer Security is 0.569 and a significant 0.000 is less than 0.05, Information Quality is 0.011 and a significant 0.895 is greater than 0.05. The results show that Consumer Security has a positive and significant effect on Trust (p1), Information Quality has a positive and insignificant effect on Trust (p2). SPSS output results with Standardized Coefficients Beta value, Consumer Security of 0.036 and significant of 0.751 which is greater than 0.05, Information Quality 0.057 and significant 0.543 which is greater than 0.05, Confidence 0.264 and significant 0.021 less than 0.05 , the results show that Consumer Security has an insignificant positive effect on Purchase Decisions. Value 0.036 is the path value (P3), Information Quality has an insignificant positive effect 0.057 is the path value (P4) and Trust has a significant positive effect 0.264 is the path value or path (P5)